Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep26328
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the N-terminal basic motif of a eukaryotic satellite RNA virus capsid protein in replication and packaging

Abstract: Efficient replication and assembly of virus particles are integral to the establishment of infection. In addition to the primary role of the capsid protein (CP) in encapsidating the RNA progeny, experimental evidence on positive sense single-stranded RNA viruses suggests that the CP also regulates RNA synthesis. Here, we demonstrate that replication of Satellite tobacco mosaic virus (STMV) is controlled by the cooperative interaction between STMV CP and the helper virus (HV) Tobacco mosaic virus (TMV) replicas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…While theoretical arguments suggest that the details of the RNA structure are important for its efficient pack-aging in the small volume of the virus capsid [13,[21][22][23][24][25], it remains overall poorly understood how the RNA sequence chemical composition together with its length affect the compactification and the packaging efficiency. Based on simple scaling arguments, it has been shown that genome secondary structures, or more specifically branching, lower the free energy of RNA encapsidation [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While theoretical arguments suggest that the details of the RNA structure are important for its efficient pack-aging in the small volume of the virus capsid [13,[21][22][23][24][25], it remains overall poorly understood how the RNA sequence chemical composition together with its length affect the compactification and the packaging efficiency. Based on simple scaling arguments, it has been shown that genome secondary structures, or more specifically branching, lower the free energy of RNA encapsidation [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Quite interestingly, in a recent experiment on Satellite Tobacco Mosaic Virus (STMV), Sivanandam et al find that reducing the number of charges on the N-terminal section of capsid proteins through mutations results into the encapsidation of shorter RNAs than the wild type ones. However, unexpectedly a single mutation in one specific location along the N-terminal completely stops the self-assembly [13]. Investigating the nature of how and which structural details of RNA could be important for virus assembly is thus urgently required to ascertain on which point along the axis of "charge-matching" to "packaging signals" hypotheses the viruses actually drive and regulate their assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue that has not yet received a lot of attention in the theoretical virus physics literature is how the interaction between the polyanions and the RNA binding domains or ARMs is affected by the molecular weight of the former. Indeed, density functional theoretic calculations are usually done at the level of the ground-state approximation, which presumes all segments to be statistically equivalent [ 23 , 48 52 ]. This implies that end- or finite-size effects are ignored.…”
Section: Cargo Length and Encapsulation Efficiencymentioning
confidence: 99%
“…However, another change was observed in the N‐terminal one‐third of the capsid protein (position 20). The N‐terminal region of capsid proteins can play important roles in different parts of the viral cycle, that is, replication and packaging as described in the Satellite tobacco mosaic virus (STMV) (Sivanandam, Mathews, Garmann, & Erdemci‐tandogan, ) or binding and internalization as reported in the parvovirus B19 (Leisi, Di Tommaso, Kempf, & Ros, ). Combining the three substitutions could be a promising option to generate attenuated virus for the future development of a vaccine against nodavirus.…”
Section: Introductionmentioning
confidence: 99%